Ligand-Binding Architecture of Human CB2 Cannabinoid Receptor: Evidence for Receptor Subtype-Specific Binding Motif and Modeling GPCR Activation - Pei, Ying (2008)
The extensive physiological influence of transmission through the CB2 cannabinoid receptor makes this G protein-coupled receptor (GPCR) a promising therapeutic target for treating neuropathic pain, inflammation, and immune disorders. However, there is little direct structural information pertaining to either GPCR or CB2-receptor ligand recognition and activation. The present work helps characterize experimentally the ligand-binding interactions of the human CB2 (hCB2) receptor. This study illustrates how our overall experimental approach, “ligand-assisted protein structure” (LAPS), affords direct determination of the requirements for ligand binding to the hCB2 receptor and discrimination among the binding motifs for ligands that activate therapeutically relevant GPCRs.